A140 AN ATYPICAL NON-CELL AUTONOMOUS REGULATION OF GUT HOMEOSTASIS: THE CONTRIBUTION OF ENTEROCYTES-RELATED AUTOPHAGY - Nassari, S (J Can Assoc Gastroenterol, 2019)
BACKGROUND: Inflammatory bowel diseases (IBD) are multifactorial diseases associated with environmental and microbial factors as well as with specific genetic variants. Over the past years, GWAS identified various autophagy-related genes (ATG16L1, LRRK2, VAMP3) as susceptibility variants in IBD. Autophagy is an essential process, defined as the degradation and recycling of cytoplasmic components by the lysosomal machinery. Interestingly, defect in the autophagy process have been revealed in patients suffering from IBD. Although the contribution of autophagy to IBD is well established in Paneth cells, it is still unclear how enterocytes-related autophagy participate in such pathologies. Enterocytes (Ec) define the main intestinal cell population in direct contact with the lumen, thus representing an ideal target for IBD treatments. AIMS: Our goal is to characterize the effect of autophagy inhibition in Ec on gut homeostasis and its contribution in IBD initiation and development. METHODS: Drosophila is a well characterized organism with powerful genetic tool, representing an excellent model to investigate intestinal biology, as it is highly conserved with humans. Drosophila gut is composed of intestinal stem cells (ISC) that differentiate into progenitor cells that yield differentiated enteroendocrines (Ee) and Ec cells. Taking advantage of the cell specific inducible GAL4/UAS system available in drosophila, we independently depleted in Ec autophagy-related genes. In such context, various aspects of gut homeostasis were analyzed. Intestinal morphology and functional integrity were evaluated using nucleus staining (DAPI) and permeability assay. Additionally, Ec apoptosis and ISC proliferation were monitored. Furthermore, differentiated cell populations were assessed using Prospero (Ee) and Pdm1 (Ec) immunostaining. Finally, assessment of life survival effect was monitored by establishing lifespan curve. RESULTS: Our results show that silencing of the autophagy-related genes ATG16, VAMP3, ATG5, SYX17 and VAMP8 in drosophila Ec affects different facet of the intestinal epithelium, although it does not perturb either intestinal integrity or lifespan. Indeed, autophagy-related genes inhibition lead to an increase in cell density, which correlate with a gain in the rate of proliferative cells. Furthermore, we observe an increase in the rate of Ee. Such results strongly suggest a non-cell autonomous effect of Ec-related autophagy in regulating ISC proliferation and favoring Ee specification and/or differentiation, thus contributing to maintenance of gut homeostasis. CONCLUSIONS: Our data indicate that basal autophagy plays an important role in Ec to regulate intestinal homeostasis through regulation of ISC proliferation and Ee fate. Therefore, as Ec represent the major cell type of the gut, upregulating autophagy in such cells could improve IBD treatments. FUNDING AGENCIES: FRQS and CRMUS